Overexpression of exogenous biuret hydrolase in rice plants confers tolerance to biuret toxicity. (29th November 2020) - Ochiai, Kumiko; Uesugi, Asuka; Masuda, Yuki; Nishii, Megumi; Matoh, Toru
Abstract: Biuret, a common impurity in urea fertilizers, is toxic to plants, but little is known about the physiological mechanisms underlying its toxicity. Here, we analyzed biuret toxicity in rice ( Oryza sativa ) plants. We carried out uptake experiments using 15 N‐labelled biuret and demonstrated that biuret could reach sub millimolar concentrations in rice plants. We also demonstrated that the hydrolysis of biuret in plant cells could confer biuret tolerance to rice plants. This occurred because transgenic rice plants that overexpressed an exogenous biuret hydrolase cloned from a soil bacterium gained improved tolerance to biuret toxicity. Our results indicate that biuret toxicity is not an indirect toxicity caused by the presence of biuret outside the roots, and that biuret is not quickly metabolized in wild‐type rice plants. Additionally, it was suggested that biuret was used as an additional nitrogen source in transgenic rice plants, because biuret hydrolase ‐overexpressing rice plants accumulated more biuret‐derived N, as compared to wild‐type rice.